Strategi Guru Pendidikan Pancasila dalam Menanamkan Nilai Humanistik dalam Kurikulum Merdeka di SMA Negeri 8 Tangerang Selatan - Ramadhan, Sultan Maulana; Pirmansyah, Deni; Narwastu, Efrata Ezra; Safitri, Lusi; Septhiani, Najma Fariha (Innovations in Multidisciplinary Education Journal, 2025)
This study aims to analyze the strategies employed by Pancasila Education teachers in instilling humanistic values within the Merdeka Curriculum at SMA Negeri 8 South Tangerang, as well as to identify the challenges encountered in its implementation. The background of this research is based on the phenomenon of students’ individualistic attitudes influenced by technology, the lack of parental supervision, and differences in teachers’ approaches to learning. This study employed a qualitative method with a descriptive approach. Data were collected through observation, in-depth interviews, and documentation, and were analyzed using Miles and Huberman’s model, which consists of data reduction, data display, and conclusion drawing. The findings reveal that the strategies for instilling humanistic values were carried out through case-based learning, group discussions, and project-based learning, emphasizing six core values: respecting others’ opinions, cooperation, self-sacrifice, caring for others, mutual assistance, and solidarity. The challenges encountered included internal factors such as students’ individualistic attitudes, and external factors such as social environment influences, popular culture, and the limited role of parents. Nevertheless, these obstacles can be overcome through personal approaches, motivation, and the creation of a conducive classroom atmosphere. This study provides implications for teachers, schools, and parents to collaborate in strengthening the cultivation of humanistic values, thereby supporting the achievement of national education goals in shaping a generation with noble character.